Presymptomatic cognition and endophenotypic traits of neurodegenerative disorders of the motor system - Peelo, Colm Gabriel (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Background: Neurodegenerative diseases of the motor system, such as Huntington's disease (HD) and Amyotrophic Lateral Sclerosis (ALS), are traditionally defined by their respective motor symptoms. However, research increasingly recognises a broader and more complex phenotype, including heterogeneous cognitive and behavioural features. The genetic nature of these disorders offers a unique window to study symptom emergence and disease progression. Clinical neuropsychology plays a critical role in characterising extramotor symptoms and identifying early markers, with implications for diagnosis, staging, prognosis, and trial readiness. Methods: This thesis employs comprehensive multi-domain neuropsychological assessment across several studies in ALS and HD to evaluate a transdiagnostic approach to early phenotyping and endophenotyping for disease liability in at-risk populations. Cross-sectional and longitudinal designs enable the investigation of stable traits, disease progression, and the temporal evolution of cognitive and behavioural phenotypes. Results: The Edinburgh Cognitive and Behavioural ALS Screen (ECAS), administered at patients' first visit to the National MND Clinic, is the gold-standard cognitive screening tool in ALS. The first study quantified the impact of subjective distress on cognitive performance in pwALS (n=60). While distress levels on the Distress Thermometer were high, they did not affect ECAS scores. Distress was, however, associated with carer-reported apathy. ALS has a complex genetic basis. Ten percent of all cases and 40% of familial ALS (fALS) are caused by C9orf72. Prior work has identified cognitive trait differences in unaffected first- and second-degree relatives of fALS patients, suggesting cognitive endophenotypes linked to genetic liability. Two studies expanded on these findings. The first replicated Phase 1 results in a new sample of fALS relatives (n=67) and healthy controls (n=37), confirming particularly confrontation naming differences. The second reassessed a Phase 1 cohort (n=52) after 4-6 years to examine temporal stability and the effects of C9orf72 carriership. Traits remained lower than controls but did not decline, and no differences emerged by gene status, supporting their validity as putative cognitive endophenotypes. HD-Cognition is a longitudinal study examining cognitive and behavioural change in premanifest and early-HD, with a focus on executive and social cognitive function. While manifest HD (manHD) participants showed globally reduced scores, premanifest HD (preHD) participants displayed subtle but measurable differences in processing speed and working memory. Social cognitive performance was associated with disease progression and declined over time alongside executive tasks. Apathy is common in ALS and HD and correlates with cognitive outcomes and prognosis. Using the Dimensional Apathy Scale (DAS), profiles were examined in pwALS (n=171), PwHD (n=44), and controls (n=33). Initiation apathy was common to both disorders; Executive apathy was elevated in HD. These profiles corresponded to cognitive domains, consistent with hypothesised neuroanatomical mechanisms, and were stable over time in HD. There is no validated cognitive screening tool for HD, despite early non-motor presentation. The ECAS, though developed for ALS, demonstrated excellent convergent validity, sensitivity, specificity, and longitudinal sensitivity in PwHD. Further validation is needed, but the ECAS shows strong potential for HD. Conclusion: These studies advance the neuropsychological characterisation of genetic liability and early phenotypic expression in ALS and HD, supporting a domain based, dimensional model of cognitive and behavioural change with clinical and translational relevance.
APPROVED
Keywords: ALS; Huntington's disease; Neuropsychology; Cognition; Endophenotypes